2000
DOI: 10.1067/mhn.2000.111356
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Ki‐67 index and some clinical aspects of acoustic neuromas (vestibular schwannomas)

Abstract: Evaluation of the proliferation activity of neuromas has a practical meaning when there are doubts about the complete resection of the tumor. Evaluation of the clinical aspects connected with increased proliferation activity may have a much broader application. The aim of this study was to correlate selected clinical and radiologic aspects of vestibular schwannomas with the results of the Ki-67 index. The studied group included 23 males and 20 females. Unilateral neuromas were stated in 38 cases (mean age, 52.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 7 publications
1
28
2
2
Order By: Relevance
“…Numerous observations indicate that EOP and opiate agonists suppress the activity of TIDA neurons by activation of µ- and/or ĸ-receptors [49, 50, 51, 52], thereby increasing the prolactin secretion [53, 54]. In the present study, we did not find an inverse correlation between prolactin levels and DOPAC/DA ratio after DAMGO or β-END administration.…”
Section: Discussioncontrasting
confidence: 41%
“…Numerous observations indicate that EOP and opiate agonists suppress the activity of TIDA neurons by activation of µ- and/or ĸ-receptors [49, 50, 51, 52], thereby increasing the prolactin secretion [53, 54]. In the present study, we did not find an inverse correlation between prolactin levels and DOPAC/DA ratio after DAMGO or β-END administration.…”
Section: Discussioncontrasting
confidence: 41%
“…An increase in Ki-67, which is an index of nuclear proliferation, was shown to correlate with the growth of solid schwannomas on MRI (93). Higher rates of tumor recurrence have also been suggested in tumors with an increased rate of nuclear proliferation and mitotic indexes, although the supporting data for this claim are not conclusive (94).…”
Section: Immunohistochemical Markers Of Growth In Vestibular Schwannomentioning
confidence: 93%
“…One possible explanation for these conflicting literature reports is that the assessment of proliferation indexes can be influenced by the point of time when the operation is performed and the tissue becomes available for analysis, since many VS do not grow continuously but can remain stable over a long period of time [2]. Niemczyk et al [34] have reported in a study of 12 VS that the group of tumors which had been shown to grow at the time of surgical removal had a higher proliferation index than the group of stable (nongrowing) tumors. A further factor that may influence the value of the assessed Ki-67 index is the exact location of the biopsy taken.…”
Section: Discussionmentioning
confidence: 99%